Chinese Civilization in the Making, 1766–221 BC - Li, Jun. author. aut Link
IX, 206 p.
Keywords: This book provides a fresh interpretation of how Chinese civilization was created and transformed in the process of its early formation (1766-221 BC). It describes the principal features of that civilization which had a profound impact on the later development of Chinese history. In particular, it discusses in detail the main characteristics of the social and political organizations of that period, and argues that, contrary to the traditional interpretation, economic development in ancient China had its own dynamism.